Q: How do you factor 3x2 - x - 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(3x - 5)(x + 2)

3x3 - 3x2 + 2x - 2 = 3x2(x - 1) + 2(x - 1) = (3x2 + 2)(x - 1)

3x2+7-6 = (3x-2)(x+3) when factored

3x2-x-2 = (3x+2)(x-1)

x(x + 2)(x - 5)

Related questions

x(3x-2)

(x + 2)(3x - 7)

(3x - 5)(x + 2)

3x2-9x-30 =3x2+6x-15x-30 =3x(x+2)-15(x+2) =(3x-15)(x+2) OR 3(x - 5)(x+2)

3x2 + 2x - 8 = 3x2 + 6x - 4x - 8 = 3x(x+2) - 4(x+2) = (3x-4)*(x+2)

3x2 - 5x - 2 can be factored into (3x + 1) (x - 2)

3x3 - 3x2 + 2x - 2 = 3x2(x - 1) + 2(x - 1) = (3x2 + 2)(x - 1)

x3 + 3x2 - 6x - 8 = (x - 2)(x2 + 5x + 4) = (x - 2)(x + 1)(x + 4)

-(x + 2)(3x + 4)

3x2+13x-10 = (3x-2)(x+5) when factored

factor out a 3x 3x(x-3)=3x2-9x

3x2+7-6 = (3x-2)(x+3) when factored